Secondary battery diaphragm, preparation method thereof and secondary battery

By applying the organic coating and adding the inorganic coating on the lithium battery separator, the problems of short-circuiting electrodes and low conductivity during high heat shrinkage are solved, and the uniform current distribution and cycle stability of the battery are improved.

CN119208906APending Publication Date: 2024-12-27HIGHPOWER TECH HUIZHOU
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411505207.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-25
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

The existing lithium battery separators are prone to short-circuiting the electrodes when they shrink at high heat, and due to poor hydrophobicity and wettability, they lead to low ionic conductivity, which affects battery performance.

Method used

The dot coating method is used to coat both sides of the base film of the lithium battery separator, and the inorganic coating is added on the basis of the inorganic coating to control the coating thickness and breathability to improve the bond between the separator and the electrode sheet. Force and current are evenly distributed.

Benefits of technology

The adhesion between the separator and the electrode sheet is improved, the influence of the coating on the performance of the base film is reduced, the uniform distribution of current is improved, and the battery's high-current discharge performance and cycle stability are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208906A_ABST
    Figure CN119208906A_ABST
Patent Text Reader

Abstract

The invention relates to a secondary battery diaphragm, a preparation method thereof and a secondary battery. The secondary battery diaphragm comprises a base membrane and organic coatings, the organic coatings are coated on the two side surfaces of the base membrane in a dispensing manner, and the coating rates of the organic coatings on the two side surfaces of the base membrane are different. According to the scheme provided by the invention, the binding power of the coating and the pole piece can be improved, the influence of the coating on the performance of the base film is reduced, and the uniform distribution of current is improved, so that the electrical performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of battery technology, and in particular to a secondary battery separator and a preparation method thereof, and a secondary battery. Background Art

[0002] Lithium batteries consist of four parts: positive electrode, negative electrode, electrolyte and separator. Among them, the separator acts as a barrier material between the positive and negative electrodes, blocking electrons and allowing lithium ions to pass through. Currently, polyethylene and polypropylene microporous membranes have been successfully used in lithium-ion batteries due to their good mechanical strength and chemical stability. However, their high thermal shrinkage can cause short circuits between electrodes, resulting in destructive safety issues; in addition, due to their inherent hydrophobicity, poor wettability and wetting speed, they have poor liquid retention performance, resulting in low ionic conductivity.

[0003] In the related art, inorganic coatings and organic coatings are mainly introduced on the surface of the base film to improve the heat resistance and hydrophobicity of the diaphragm, among which the organic coating coating process mainly adopts micro-gravure roller coating.

[0004] However, the surface density of micro-gravure roller coating is relatively thick, resulting in poor air permeability of the diaphragm; and during the battery cell cycle, the lithium ions penetrate the diaphragm with a large degree of tortuosity, which can easily cause excessive polarization and a large increase in internal resistance during large current charging and discharging; and the diaphragm obtained by micro-gravure roller coating has a high adhesion to the electrode, resulting in a small gap between the diaphragm and the electrode, and a low liquid retention coefficient, which can easily lead to a lack of electrolyte and lithium precipitation in the later cycle process of the battery cell. Summary of the invention

[0005] In order to solve or partially solve the problems existing in the related art, the present application provides a secondary battery separator and its preparation method and a secondary battery, which can improve the adhesion between the coating and the electrode while reducing the influence of the coating on the performance of the base film, improve the uniform distribution of current, and thus improve the electrical performance of the battery.

[0006] The first aspect of the present application provides a secondary battery separator, comprising:

[0007] Basement membrane;

[0008] The organic coating is coated on both sides of the base film by dot coating, and the coating rates of the organic coating on the two sides of the base film are different.

[0009] As an optional embodiment, the difference in coating rate of the organic coating on the two sides of the base film is 10% to 30%.

[0010] As an optional embodiment, the coating rate of the organic coating on one side of the base film is 10% to 30%, and the coating rate of the organic coating on the other side is 20% to 40%.

[0011] As an optional embodiment, the battery separator further includes an inorganic coating, which is coated on at least one side of the base film, and is disposed between the base film and the organic coating.

[0012] As an optional embodiment, the inorganic coating is coated on the side of the base film where the coating rate of the organic coating is greater.

[0013] As an optional embodiment, the thickness of the inorganic coating is 0.5 μm to 4 μm.

[0014] As an optional embodiment, the bonding strength of the organic coating with a larger coating rate is 4N / m to 8N / m, and the bonding strength of the organic coating with a smaller coating rate is 2N / m to 7N / m.

[0015] As an optional embodiment, the compression ratio of the organic coating after chemical forming and hot pressing is 10% to 35%.

[0016] As an optional embodiment, the thickness of the organic coating is 1 μm to 4 μm.

[0017] As an optional embodiment, the surface density of the organic coating is 0.1 g / m 2 ~1.5g / m 2 .

[0018] As an optional embodiment, the base film includes one of a PE film, a PP film, a PET film, and a PI film.

[0019] As an optional embodiment, the base film has a thickness of 3 μm to 12 μm.

[0020] As an optional embodiment, the air permeability of the base film is 50s / 100cc to 200s / 100cc.

[0021] As an optional embodiment, the porosity of the base film is 25% to 50%.

[0022] The second aspect of the present application provides a method for preparing a secondary battery separator, comprising:

[0023] Prepare an organic slurry, and apply the organic slurry to both sides of the base film by dot coating through two different anilox rollers; wherein the roller surfaces of the two different anilox rollers both include mesh holes distributed in an array, and the diameters of the mesh holes in the two different anilox rollers are different and / or the spacings between the mesh holes are different;

[0024] After drying, organic coatings with different coating rates are obtained on both sides of the base film, and a secondary battery separator is formed.

[0025] As an optional embodiment, all the mesh holes on the roller surfaces of the two different anilox rollers are evenly spaced in the axial direction and evenly spaced in the circumferential direction.

[0026] As an optional embodiment, the mesh holes in the two different anilox rollers are both circular or elliptical.

[0027] As an optional embodiment, one of the two different anilox rollers is used to match an organic coating with a higher coating rate, and the spacing between two adjacent mesh holes in the anilox roller is 80μm to 1350μm, and the diameter of the mesh holes is 50μm to 450μm; the other anilox roller is used to match an organic coating with a lower coating rate, and the spacing between two adjacent mesh holes in the anilox roller is 70μm to 950μm, and the diameter of the mesh holes is 50μm to 450μm.

[0028] As an optional embodiment, the organic slurry includes an organic polymer, an inorganic oxide and an organic solvent; the solid content of the organic slurry is 5% to 30%, and the mass percentage of the organic polymer to the total solid content in the organic slurry is 80% to 95%, and the mass percentage of the inorganic oxide to the total solid content in the organic slurry is 5% to 20%. The third aspect of the present application provides a secondary battery, comprising: a positive electrode, a negative electrode and a separator, the separator is arranged between the positive electrode and the negative electrode, and the separator is the secondary battery separator described above or the secondary battery separator prepared by the preparation method of the secondary battery separator described above, and the organic coating on the two sides of the base film has a large coating rate facing the positive electrode.

[0029] The technical solution provided by this application may have the following beneficial effects:

[0030] In the present application, the organic coating is applied to both sides of the base film by spot coating, so that the organic coating applied on both sides of the base film is not fully covered. Compared with micro-gravure roller coating, since there are distribution gaps in the organic coating on the side of the base film, it has little effect on the air permeability of the base film. At the same time, the gaps can also provide better channels for the circulation and infiltration of the electrolyte, the dynamic performance of the diaphragm is better, and the internal resistance increase rate during the cycle is lower; compared with spraying, the organic coating obtained by spot coating has a higher coating rate, which can ensure that the diaphragm has better adhesion, and the thickness and air permeability of the diaphragm are more uniform. Therefore, the diaphragm of the present application can improve the adhesion between the coating and the pole piece, reduce the influence of the coating on the performance of the base film, improve the uniform distribution of current, and thus improve the high current discharge performance of the battery.

[0031] Furthermore, in the present application, the coating rates of the organic coatings on the two sides of the base film are different, so that the adhesion of the organic coatings on the two sides of the base film can be different to match the different requirements of the positive and negative electrodes for adhesion. Since the bonding requirements on the positive electrode side in the battery cell are high and the appearance of the battery cell needs to be kept from deforming, the organic coating with a large coating rate can be matched on the positive electrode side; while the negative electrode bonding performance requirements are low, the organic coating with a small coating rate can be matched on the positive electrode side to buffer the expansion of the negative electrode and improve the liquid retention rate.

[0032] It should be understood that the foregoing general description and the following detailed description are exemplary and explanatory only and are not restrictive of the present application. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] The above and other objects, features and advantages of the present application will become more apparent by describing in more detail exemplary embodiments of the present application in conjunction with the accompanying drawings, wherein the same reference numerals generally represent the same components in the exemplary embodiments of the present application.

[0034] Figure 1 It is a schematic diagram of a process for preparing a secondary battery separator shown in an embodiment of the present application;

[0035] Figure 2 It is a schematic diagram of the structure of the anilox roller shown in an embodiment of the present application.

[0036] In the figure: 1, anilox roller; 10, mesh. DETAILED DESCRIPTION

[0037] The embodiments of the present application will be described in more detail below with reference to the accompanying drawings. Although the embodiments of the present application are shown in the accompanying drawings, it should be understood that the present application can be implemented in various forms and should not be limited by the embodiments described herein. On the contrary, these embodiments are provided to make the present application more thorough and complete, and to fully convey the scope of the present application to those skilled in the art.

[0038] The terms used in this application are for the purpose of describing specific embodiments only and are not intended to limit this application. The singular forms of "a", "said" and "the" used in this application and the appended claims are also intended to include plural forms unless the context clearly indicates other meanings. It should also be understood that the term "and / or" used herein refers to and includes any or all possible combinations of one or more associated listed items.

[0039] It should be understood that although the terms "first", "second", "third", etc. may be used in this application to describe various information, this information should not be limited to these terms. These terms are only used to distinguish the same type of information from each other. For example, without departing from the scope of this application, the first information may also be referred to as the second information, and similarly, the second information may also be referred to as the first information. Thus, the features defined as "first" and "second" may explicitly or implicitly include one or more of the features. In the description of this application, the meaning of "multiple" is two or more, unless otherwise clearly and specifically defined.

[0040] In the related technology, inorganic coating and organic coating are mainly introduced on the surface of the base film to improve the heat resistance and hydrophobicity of the diaphragm. Among them, the organic coating coating process mainly adopts micro-gravure roller coating. However, the surface density of micro-gravure roller coating is relatively thick, resulting in poor air permeability of the diaphragm; and in the process of battery cell cycle, the tortuosity of lithium ion penetration through the diaphragm is relatively large, which is easy to cause excessive polarization and a large increase in internal resistance during high current charging and discharging; and the diaphragm obtained by micro-gravure roller coating has a high adhesion with the pole piece, which makes the gap between the diaphragm and the pole piece small, and the liquid retention coefficient is low, resulting in the lack of electrolyte and lithium precipitation in the later cycle of the battery cell cycle.

[0041] In view of the above problems, the embodiments of the present application provide a secondary battery separator, which can improve the adhesion between the coating and the electrode, reduce the influence of the coating on the performance of the base film, improve the uniform distribution of current, and thus improve the electrical performance of the battery.

[0042] An embodiment of the present application provides a secondary battery separator, comprising a base film and an organic coating, wherein the organic coating is applied to both sides of the base film by spot coating, and the coating rates of the organic coating on the two sides of the base film are different.

[0043] The base film in the embodiment of the present application is a porous polymer film, which may include one of a PE film, a PP film, a PET film, and a PI film.

[0044] The organic coating in the embodiment of the present application can be an organic polymer coating, for example, it can be at least one of polyvinylidene fluoride, polyvinylidene fluoride copolymer, polymethyl methacrylate, polymethyl methacrylate copolymer, polyvinyl alcohol, polyvinyl acetate, styrene-butadiene latex, ethylene-vinyl acetate copolymer, sodium carboxymethyl cellulose and polyvinyl pyrrolidone organic polymers.

[0045] The coating rate in the embodiments of the present application may refer to the percentage of the distribution area of ​​the organic coating on one side of the base film to the area of ​​the side.

[0046] In the embodiment of the present application, the organic coating is applied to both sides of the base film by spot coating, so that the organic coating applied on both sides of the base film is not fully covered. Compared with micro-gravure roller coating, since there are distribution gaps in the organic coating on the side of the base film, it has little effect on the air permeability of the base film. At the same time, the gaps can also provide better channels for the circulation and infiltration of the electrolyte, the dynamic performance of the diaphragm is better, and the internal resistance increase rate during the cycle is lower; compared with spraying, the organic coating obtained by spot coating has a higher coating rate, which can ensure that the diaphragm has better adhesion, and the thickness and air permeability of the diaphragm are more uniform. Therefore, the diaphragm of the embodiment of the present application can improve the adhesion between the coating and the pole piece, reduce the influence of the coating on the performance of the base film, improve the uniform distribution of current, and thus improve the high current discharge performance of the battery.

[0047] Furthermore, in the embodiment of the present application, the coating rates of the organic coatings on the two sides of the base film are different, so that the adhesion of the organic coatings on the two sides of the base film can be different to match the different requirements of the positive and negative electrodes for adhesion. Since the bonding requirements on the positive electrode side in the battery cell are high and the appearance of the battery cell needs to be kept from deforming, the organic coating with a large coating rate can be matched on the positive electrode side; while the negative electrode bonding performance requirements are low, the organic coating with a small coating rate can be matched on the positive electrode side to buffer the expansion of the negative electrode and improve the liquid retention rate.

[0048] As an optional embodiment, the difference in coating rate of the organic coatings on the two sides of the base film is 10% to 30%.

[0049] In the embodiment of the present application, the air permeability and adhesion ability of the diaphragm can be balanced by controlling the difference between the coating rate of the organic coating with a large coating rate and the coating rate of the organic coating with a small coating rate on both sides of the base film. If the difference between the two is too low, the air permeability of the diaphragm may be poor, and if the difference between the two is too high, the adhesion of the diaphragm may be too low. Therefore, controlling the difference between the two within the above-mentioned limited range can meet both the air permeability and adhesion requirements.

[0050] Furthermore, the coating rate of the organic coating on one side of the base film is 10% to 30%, and the coating rate of the organic coating on the other side is 20% to 40%.

[0051] It can be understood that the distribution area of ​​the organic coating on one side of the base film accounts for 10% to 30% of the area of ​​the side, and the distribution area of ​​the organic coating on the other side of the base film accounts for 20% to 40% of the area of ​​the side.

[0052] In an embodiment of the present application, the coating rate of the organic coating on one side of the base film may be 10%, 15%, 20%, 25%, 30% or any value within the above-defined range, and the coating rate of the organic coating on the other side of the base film may be 20%, 25%, 30%, 35%, 40% or any value within the above-defined range, which is not limited in the present application.

[0053] As a preferred embodiment, the bonding strength of the organic coating with a larger coating rate is 4N / m to 8N / m, and the bonding strength of the organic coating with a smaller coating rate is 2N / m to 7N / m.

[0054] Since the bonding strength of the organic coating is positively correlated with the coating coating rate, the bonding strength of the organic coating with a larger coating rate is greater than the bonding strength of the organic coating with a smaller coating rate.

[0055] As an optional embodiment, the battery separator may further include an inorganic coating, which is coated on at least one side of the base film and is disposed between the base film and the organic coating.

[0056] The inorganic coating in the embodiment of the present application can be an inorganic heat-resistant coating to prevent the base film from shrinking at high temperatures, resulting in the problem of short circuit caused by contact between the positive and negative electrodes. In addition, the organic coating is dotted on the outer surface of the inorganic coating to increase the adhesion between the diaphragm and the electrode piece without affecting the air permeability of the diaphragm.

[0057] As a preferred embodiment, the inorganic coating is coated on the side of the base film where the coating rate of the organic coating is greater.

[0058] Since the heat resistance of the positive electrode is worse than that of the negative electrode, the inorganic coating is arranged on the side of the organic coating with a larger coating rate, which can correspond to the side bonded with the positive electrode, thereby improving the heat resistance of the positive electrode side of the separator.

[0059] As a preferred embodiment, the inorganic coating is made of inorganic slurry, and the inorganic slurry includes inorganic ceramics, a binder, a dispersant and a thickener.

[0060] In the embodiment of the present application, the inorganic ceramic includes one or more of aluminum oxide, barium titanate, titanium dioxide, silicon dioxide, magnesium hydroxide, boehmite, zirconium oxide or silicon carbide.

[0061] Thickeners include cellulose and polyacrylamide, polyvinyl alcohol, polyvinyl pyrrolidone, polyacrylic acid, sodium polyacrylate, etc. Cellulose thickeners include one or more of methyl cellulose, hydroxypropyl methyl cellulose and carboxymethyl cellulose. After inorganic ceramics are dispersed and ground, thickeners are added to keep the inorganic ceramics stable.

[0062] The dispersant may be ammonium polyacrylate, which is dissolved in water or ethanol and then added into the inorganic ceramic for stirring and dispersion.

[0063] The binder can be polyacrylate and / or polyacrylic acid, and its function is to firmly bond the base film and the inorganic slurry.

[0064] As a preferred embodiment, the thickness of the inorganic coating is 0.5 μm to 4 μm.

[0065] In the embodiments of the present application, the thickness of the inorganic coating layer may be 0.5 μm, 1 μm, 2 μm, 3 μm, 4 μm or any value within the above-defined range, which is not limited in the present application.

[0066] As a preferred embodiment, the compression ratio of the organic coating after chemical forming and hot pressing is 10% to 35%.

[0067] In the embodiments of the present application, the compression ratio of the organic coating after hot pressing can be 10%, 15%, 20%, 25%, 30%, 35% or any value within the above-defined range, and the present application does not impose any limitation on this.

[0068] As a preferred embodiment, the thickness of the organic coating is 1 μm to 4 μm.

[0069] In the embodiments of the present application, the thickness of the organic coating may be 1 μm, 2 μm, 3 μm, 4 μm or any value within the above-defined range, and the present application does not impose any limitation on this.

[0070] As a preferred embodiment, the surface density of the organic coating is 0.1 g / m 2 ~1.5g / m 2 .

[0071] In the embodiment of the present application, the surface density of the organic coating can be 0.1 g / m 2 , 0.2g / m 2 , 0.4g / m 2 , 0.5g / m 2 , 1g / m 2 , 1.2g / m 2 , 1.5g / m 2 Or any numerical value within the above-defined range, which is not limited in this application.

[0072] As a preferred embodiment, the base film includes one of a PE film, a PP film, a PET film, and a PI film.

[0073] In the embodiment of the present application, the base film may also be a composite film formed by combining at least one of a PE film, a PP film, a PET film, and a PI film.

[0074] As a preferred embodiment, the thickness of the base film is 3 μm to 12 μm.

[0075] In the embodiments of the present application, the thickness of the base film may be 3 μm, 4 μm, 5 μm, 7 μm, 9 μm, 12 μm or any value within the above-specified range, and the present application does not impose any limitation on this.

[0076] As a preferred embodiment, the air permeability of the base film is 50s / 100cc to 200s / 100cc.

[0077] In the embodiments of the present application, the air permeability of the base film may be 50s / 100cc, 100s / 100cc, 150s / 100cc, 170s / 100cc, 200s / 100cc or any value within the above-defined range, and the present application does not impose any limitation on this.

[0078] As a preferred embodiment, the porosity of the base film is 25% to 50%.

[0079] In the embodiments of the present application, the porosity of the base film may be 25%, 30%, 40%, 50% or any value within the above-defined range, and the present application does not impose any limitation on this.

[0080] Corresponding to the aforementioned application function realization method embodiment, the present application also provides a method for preparing a secondary battery separator, a secondary battery and corresponding embodiments.

[0081] See also Figure 1 The present application also provides a method for preparing a secondary battery separator, comprising:

[0082] S1. Prepare an organic slurry, and apply the organic slurry to both sides of the base film by dot coating through two different anilox rollers; wherein the roller surfaces of the two different anilox rollers have mesh holes distributed in an array, and the diameters of the mesh holes in the two different anilox rollers are different and / or the spacing between the mesh holes is different.

[0083] In the embodiment of the present application, the organic slurry is spot-coated on both side surfaces of the base film through two different anilox rollers. Since the roller surfaces of the two different anilox rollers have mesh holes distributed in an array, there can be gaps between the mesh holes. The organic slurry adhered to the mesh holes is transferred to the side surface of the base film through the rotation of the anilox rollers, so that the organic slurry is distributed in a dot array on the base film. Since the mesh holes in the two different anilox rollers have different diameters and / or different mesh hole spacings, the coating rates of the organic slurry on the two side surfaces of the base film can be different.

[0084] S2. After drying, an organic coating with different coating rates is obtained on both sides of the base film, and a secondary battery separator is formed.

[0085] After drying, the organic slurry distributed in a dot array on both sides of the base film solidifies and adheres to the base film to form an organic coating. Finally, the base film and the organic coatings on its two sides with different coating rates together form a secondary battery separator.

[0086] In the embodiment of the present application, the organic coating is applied to both sides of the base film by two different anilox rollers in a dot coating manner, so that the organic coating applied on both sides of the base film is not fully covered. Compared with micro-gravure roller coating, since there are distribution gaps in the organic coating on the side of the base film, it has little effect on the air permeability of the base film. At the same time, the gaps can also provide better channels for the circulation and infiltration of the electrolyte, the dynamic performance of the diaphragm is better, and the internal resistance increase rate during the cycle is lower; compared with spraying, the dot coating method obtains a higher coating rate of the organic coating, which can ensure that the diaphragm has better adhesion, and the thickness and air permeability of the diaphragm are more uniform. Therefore, the diaphragm prepared in the embodiment of the present application can improve the adhesion between the coating and the pole piece, reduce the influence of the coating on the performance of the base film, improve the uniform distribution of current, and thus improve the high current discharge performance of the battery.

[0087] Furthermore, the mesh diameters of the two different anilox rollers in the embodiment of the present application are different and / or the mesh spacings are different, so that the coating rate, thickness and coating surface density of the organic coating on the two sides of the base film are different, which can make the adhesion of the organic coating on the two sides of the base film different, and even affect the cycle performance and electrical performance of the battery. In this way, the different requirements of the positive and negative electrodes for adhesion can be matched. Since the bonding requirements on the positive electrode side in the battery cell are high and the appearance of the battery cell needs to be kept from deforming, the organic coating with a large coating rate can be matched on the positive electrode side; and the negative electrode bonding performance requirements are low, so the organic coating with a small coating rate can be matched on the positive electrode side to buffer the expansion of the negative electrode and improve the liquid retention rate. In this way, the thickness expansion requirements of the battery cell can be met, and more blank gaps can be left through the differentiated design of the coating rate without affecting the air permeability of the base film.

[0088] As an alternative embodiment, see Figure 2 All mesh holes 10 on the roller surface of the two different anilox rollers 1 are evenly spaced in the axial direction and evenly spaced in the circumferential direction.

[0089] The anilox roller 1 in the embodiment of the present application has a twill pattern, which can be understood as all the mesh holes 10 being distributed in an array along an inclined axis at a certain angle to the axial direction. In this way, even if the organic slurry flows or even overflows in the mesh holes, it will not flow into other mesh holes and will not affect other mesh holes, thereby making the slurry distribution in each mesh hole more even.

[0090] As an optional embodiment, the mesh openings in the two different anilox rollers are both circular or elliptical.

[0091] The mesh in the embodiment of the present application is preferably circular.

[0092] As a preferred embodiment, one of the two different anilox rollers is used to match an organic coating with a higher coating rate, and the spacing between two adjacent mesh holes in the anilox roller is 80μm to 1350μm, and the diameter of the mesh holes is 50μm to 450μm. The other anilox roller is used to match an organic coating with a lower coating rate, and the spacing between two adjacent mesh holes in the anilox roller is 70μm to 950μm, and the diameter of the mesh holes is 50μm to 450μm.

[0093] The embodiment of the present application can adjust the coating rate, thickness and coating surface density of the organic coating on both sides of the base film by adjusting the mesh spacing and diameter of the two anilox rollers to adapt to different usage requirements.

[0094] As an optional embodiment, the organic slurry includes an organic polymer, an inorganic oxide and an organic solvent; the solid content of the organic slurry is 5% to 30%, and the mass percentage of the organic polymer and the total solid content in the organic slurry is 80% to 95%, and the mass percentage of the inorganic oxide and the total solid content in the organic slurry is 5% to 20%.

[0095] In the embodiment of the present application, the sum of the mass percentages of the organic polymer and the inorganic oxide is the total solid amount in the organic slurry, and is calculated as 100%, wherein the mass percentage of the organic polymer in the total solid amount in the organic slurry is 80% to 95%, and the mass percentage of the inorganic oxide in the total solid amount in the organic slurry is 5% to 20%. In the embodiment of the present application, the organic polymer can be selected from at least one of polyvinylidene fluoride, polyvinylidene fluoride copolymer, polymethyl methacrylate, polymethyl methacrylate copolymer, polyvinyl alcohol, polyvinyl acetate, styrene-butadiene latex, ethylene-vinyl acetate copolymer, sodium carboxymethyl cellulose and polyvinyl pyrrolidone.

[0096] In the embodiment of the present application, the inorganic oxide can be selected from at least one of alumina, boehmite, aluminum hydroxide, silicon dioxide, zirconium oxide, and magnesium hydroxide.

[0097] The solid content of the organic slurry in the embodiment of the present application may refer to the mass percentage of the organic polymer, inorganic oxide and solvent in the organic slurry, and the solid content of the organic slurry in the embodiment of the present application is relatively high, which can reduce the fluidity of the organic slurry and prevent the organic slurry distributed in the dot matrix on the base film from aggregating with each other due to high fluidity before solidification, resulting in the gaps between the array points being filled, affecting the air permeability of the base film.

[0098] An embodiment of the present application also provides a secondary battery, including a positive electrode, a negative electrode and a separator, wherein the separator is arranged between the positive electrode and the negative electrode, and the separator is the above-mentioned secondary battery separator or a secondary battery separator prepared by the above-mentioned preparation method of the secondary battery separator.

[0099] In order to further understand the present invention, the present application is described below in conjunction with embodiments. These embodiments are only used to illustrate the present application and are not used to limit the scope of the present application.

[0100] Embodiment 1:

[0101] 1. Preparation of diaphragm

[0102] (1) Preparation of inorganic slurry:

[0103] The dispersant is dispersed with solvent water, and then the inorganic ceramic is added for dispersion and stirring; then the thickener is added and stirred evenly to adjust the viscosity of the slurry, and then ground after stirring and dispersing evenly; after grinding, a certain amount of binder and wetting agent are added, and after mixing evenly, an inorganic coating slurry with a solid content of 32% is obtained. Among them, the inorganic ceramic is alumina, the binder is polyacrylate, the dispersant is ammonium polyacrylate, and the thickener is carboxymethyl cellulose, and the mass percentages are: 29.3%, 2%, 0.2%, and 0.5% respectively.

[0104] (2) Coating of inorganic slurry:

[0105] A wet asynchronous double-stretched polyethylene diaphragm with a thickness of 4 μm, a porosity of 35%, and an air permeability of 100 s / 100 cc was selected. The inorganic slurry prepared in step (1) was coated on one side of the base film by micro-gravure roller coating. The coating speed was 50 m / min. After drying, a base film coated with an inorganic coating was obtained, and the thickness of the inorganic coating was 1 μm.

[0106] (3) Preparation of organic slurry:

[0107] Weigh 12% of an organic polymer and 3% of an inorganic oxide, add 85% of an organic solvent, mix and stir for 2 hours to form an organic slurry with a solid content of 15%. The organic polymer is a PVDF polymer, the inorganic oxide is aluminum oxide, and the total mass percentage of the organic polymer and the solid in the organic slurry is 80%, and the total mass percentage of the inorganic oxide and the solid in the organic slurry is 20%.

[0108] (4) Coating of organic slurry:

[0109] According to the formula and process obtained in Table 1, the organic slurry prepared in step (3) is coated on both sides of the base film coated with the inorganic coating obtained in step (2) by two different anilox rollers at a rate of 20 m / min. After washing and drying, organic coatings with different coating rates on both sides of the base film are obtained to form a secondary battery separator.

[0110] 2. Preparation of battery cells

[0111] The above-mentioned separator is placed between the positive electrode sheet and the negative electrode sheet, and then the sandwich structure composed of the positive electrode sheet, the negative electrode sheet and the separator is wound, and then the wound body is flattened and placed in an aluminum-plastic shell, and the aluminum-plastic shell is sealed after welding the pole ears to obtain a battery cell to be injected with liquid; a commercially available electrolyte is injected into the battery cell, and the lithium-ion battery is prepared by sealing, aging and forming.

[0112] Example 2 to Example 7, and Comparative Example 1 to Comparative Example 2:

[0113] The secondary battery separators and lithium ion batteries of Examples 2 to 7 and Comparative Examples 1 and 2 were prepared according to the formulations and processes in Table 1.

[0114] 3. Performance Test

[0115] The diaphragms prepared in the above-mentioned embodiments and comparative examples were subjected to corresponding performance tests according to the following methods, and the test results in Table 2 were obtained by calculation.

[0116] (1) Adhesion test:

[0117] Cut the positive electrode sheet / negative electrode sheet of 100mm×15mm and the separator of 150mm×25mm, place the positive electrode sheet / negative electrode sheet on the separator, and then hot press for 5min at 1.0MPa and 90℃.

[0118] After the hot pressing is completed, the separator and the positive electrode sheet / negative electrode sheet are clamped by a universal testing machine and a peeling test is performed at 180°C. The peeling speed is 300 mm / min, and the average bonding strength is read.

[0119] (2) Electrical performance test:

[0120] 1. 45℃ 2C stage charge / 1.5CP discharge performance:

[0121] The prepared battery cell was placed in a 45°C oven for 2 hours, then charged at 2C constant current for 15 minutes, 0.7C to 4.48V, 0.05C cut-off, left standing for 10 minutes, and discharged at 1.5CP to 3.0V, left standing for 10 minutes; the charge and discharge were repeated for 600 cycles, and the discharge capacity C at the 600th cycle was calculated. 600 , the capacity retention rate at the 600th week is the discharge capacity C at the 600th week 600 The ratio of discharge capacity to the first week C 600 / C1.

[0122] 2. 25℃ 2C stage charge / 1.5CP discharge performance:

[0123] The prepared battery cell was placed in a 25°C oven for 2 hours, then charged at 2C constant current for 15 minutes, 0.7C to 4.48V, 0.05C cut-off, left standing for 10 minutes, and discharged at 1.5CP to 3.0V, left standing for 10 minutes; the charge and discharge cycle was repeated for 1000 cycles, and the discharge capacity C at the 1000th cycle was calculated. 1000 , the capacity retention rate at the 1000th week is the discharge capacity C at the 1000th week 1000 The ratio of discharge capacity to the first week C 1000 / C1.

[0124] 3. 25℃ 5C rate discharge performance:

[0125] The prepared battery cell was placed in a 25°C oven for 2 hours, and then charged and discharged in the following ways (a) to (q):

[0126] (a) Discharge at 0.2C to 3.0V and let stand for 10 minutes. (b) Fully charge at 0.7C, cut-off current 0.05C, let stand for 10 minutes.

[0127] (c) Discharge at 0.2C to 3.0V, let stand for 10min, and record the corresponding capacity. (d) Fully charged at 0.7C, cut-off current 0.05C, let stand for 10min. (e) Discharge at 0.5C to 3.0V, let stand for 10min, and record the corresponding capacity. (f) Fully charged at 0.7C, cut-off current 0.05C, let stand for 10min. (g) Discharge at 1.0C to 3.0V, let stand for 10min, and record the corresponding capacity. (h) Fully charged at 0.7C, cut-off current 0.05C, let stand for 10min. (i) Discharge at 1.5C to 3.0V, let stand for 10min, and record the corresponding capacity. (j) Fully charged at 0.7C, cut-off current 0.05C, let stand for 10min. (k) Discharge at 2.0C to 3.0V, let stand for 10min, and record the corresponding capacity. (l) Fully charged at 0.7C, cut-off current 0.05C, let stand for 10min. (m) Discharge at 3.0C to 3.0V, let stand for 10min, and record the corresponding capacity. (n) Fully charge at 0.7C, cut-off current 0.05C, let stand for 10min. (o) Discharge at 4.0C to 3.0V, let stand for 10min, and record the corresponding capacity. (p) Fully charge at 0.7C, cut-off current 0.05C, let stand for 10min. (q) Discharge at 5.0C to 3.0V, let stand for 10min, and record the corresponding capacity. The ratio of the discharge capacity at this rate to the discharge capacity at 0.2C is taken as the capacity retention rate.

[0128] Table 1 Formulation and process table

[0129]

[0130]

[0131]

[0132] Table 2 Test results

[0133]

[0134]

[0135] Combining the data in Table 1 and Table 2, by comparing Examples 1 to 3, it can be seen that as the coating rate of the organic coating on the positive electrode side increases, the air permeability of the battery decreases, and the bonding strength and electrical performance are improved. And by comparing Examples 3 to 5, it can be seen that as the coating rate of the organic coating on the negative electrode side increases, the air permeability of the battery decreases, and the bonding strength and electrical performance are improved.

[0136] By comparing Example 5 and Example 6, it can be seen that as the thickness of the organic coating on the positive and negative electrode sides increases, the air permeability of the battery is improved, but the bonding strength and electrical performance are reduced.

[0137] By comparing Example 5 and Example 7, it can be seen that adding an inorganic coating on the side with a larger coating rate of the organic coating can improve the bonding strength, heat resistance and electrical performance of the battery.

[0138] By comparing Examples 1 to 7 with Comparative Example 1, it is found that the use of micro-gravure roller coating for organic coating will greatly reduce the air permeability and electrical performance of the battery.

[0139] By comparing Example 5 and Comparative Example 2, it is found that when the coating rates of the organic coating on both sides of the base film are different, it has little effect on the air permeability of the battery, and can improve the bonding strength and electrical performance.

[0140] The embodiments of the present application have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes will be apparent to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The selection of terms used herein is intended to best explain the principles of the embodiments, practical applications, or improvements to the technology in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A secondary battery separator, characterized in that: include: Basement membrane; The organic coating is coated on both sides of the base film by dot coating, and the coating rates of the organic coating on the two sides of the base film are different.

2. The secondary battery separator according to claim 1, characterized in that: The difference in coating rate of the organic coating on the two sides of the base film is 10% to 30%.

3. The secondary battery separator according to claim 1 or 2, characterized in that: The coating rate of the organic coating on one side of the base film is 10% to 30%, and the coating rate of the organic coating on the other side is 20% to 40%.

4. The secondary battery separator according to claim 1, characterized in that: The battery separator further includes an inorganic coating layer, which is coated on at least one side of the base film and is disposed between the base film and the organic coating layer.

5. The secondary battery separator according to claim 4, characterized in that: The inorganic coating is coated on the side of the base film where the coating rate of the organic coating is greater; and / or the thickness of the inorganic coating is 0.5 μm to 4 μm.

6. The secondary battery separator according to claim 1, characterized in that: The bonding strength of the organic coating with a larger coating rate is 4N / m to 8N / m, and the bonding strength of the organic coating with a smaller coating rate is 2N / m to 7N / m; and / or, The compression ratio of the organic coating after chemical forming and hot pressing is 10% to 35%; and / or, The thickness of the organic coating is 1 μm to 4 μm; and / or, The surface density of the organic coating is 0.1 g / m 2 ~1.5g / m 2 and / or, The base film comprises one of a PE film, a PP film, a PET film and a PI film; and / or, The thickness of the base film is 3 μm to 12 μm; and / or, The air permeability of the base film is 50s / 100cc to 200s / 100cc; and / or, The porosity of the base film is 25% to 50%.

7. A method for preparing a secondary battery separator, characterized in that: include: Prepare an organic slurry, and apply the organic slurry to both sides of the base film by dot coating through two different anilox rollers; wherein the roller surfaces of the two different anilox rollers both include mesh holes distributed in an array, and the diameters of the mesh holes in the two different anilox rollers are different and / or the spacings between the mesh holes are different; After drying, organic coatings with different coating rates are obtained on both sides of the base film, and a secondary battery separator is formed.

8. The method according to claim 7, characterized in that All the mesh holes on the roller surfaces of the two different anilox rollers are evenly spaced in the axial direction and evenly spaced in the circumferential direction; and / or the mesh holes in the two different anilox rollers are all circular or elliptical.

9. The method according to claim 8, characterized in that One of the two different anilox rollers is used to match an organic coating with a higher coating rate, and the spacing between two adjacent mesh holes in the anilox roller is 80μm to 1350μm, and the diameter of the mesh holes is 50μm to 450μm. The other anilox roller is used to match an organic coating with a lower coating rate, and the spacing between two adjacent mesh holes in the anilox roller is 70μm to 950μm, and the diameter of the mesh holes is 50μm to 450μm.

10. The method according to any one of claims 7 to 9, characterized in that: The organic slurry includes an organic polymer, an inorganic oxide and an organic solvent; the solid content of the organic slurry is 5% to 30%, and the mass percentage of the organic polymer to the total solid content in the organic slurry is 80 to 95%, and the mass percentage of the inorganic oxide to the total solid content in the organic slurry is 5 to 20%.

11. A secondary battery, characterized in that: include: A positive electrode, a negative electrode and a separator, wherein the separator is arranged between the positive electrode and the negative electrode, and the separator is a secondary battery separator according to any one of claims 1 to 6 or a secondary battery separator prepared by the preparation method of the secondary battery separator according to any one of claims 7 to 10, and among the organic coatings on the two sides of the base film, the organic coating with a large coating rate faces the positive electrode.